The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/2045-824x-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate-related osteonecrosis of jaw (BRONJ): diagnostic criteria and possible pathogenic mechanisms of an unexpected anti-angiogenic side effect

Abstract: Recently, bisphosphonates (BPs) have been widely used in medical practice as anti-resorptive agents owing to their anti-osteoclatic action. In addition, these compounds are also used for their analgesic action and their potential anti-tumour effect. Patients treated with BPs may subsequently develop osteonecrosis of the jaw or maxillary bone after minor local trauma including dental work, recently labelled as bisphosphonate osteonecrosis of jaw (BRONJ). However, the etiopathogenic mechanisms of this pathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 40 publications
0
77
0
12
Order By: Relevance
“…On a cellular level, switching BPs in the course of treatment might make sense, as the BPs act at different points in the mevalonate pathway and have various potential to cause other biochemical effects, not only on osteoclast/osteoblast interaction but also on inhibiting angiogenesis or tissue regeneration (Sharma et al 2013). In light of our results on the similar potential of ibandronate and zoledronate to promote an ONJ within the same time frame, it might make sense to start off with or switch to a BP of an earlier generation such as pamidronate if other aspects of the patient's quality of life allow for it.…”
Section: Discussionmentioning
confidence: 99%
“…On a cellular level, switching BPs in the course of treatment might make sense, as the BPs act at different points in the mevalonate pathway and have various potential to cause other biochemical effects, not only on osteoclast/osteoblast interaction but also on inhibiting angiogenesis or tissue regeneration (Sharma et al 2013). In light of our results on the similar potential of ibandronate and zoledronate to promote an ONJ within the same time frame, it might make sense to start off with or switch to a BP of an earlier generation such as pamidronate if other aspects of the patient's quality of life allow for it.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012 Reid and Cornish [5] reviewed 2408 cases of BRONJ and reported that incidence of BRONJ after administration of IV BPs in cancer patients was 89 % while rest 11 % had only received oral BPs. In contrast to the above report Sharma et al [6] in 2013 reported that the incidence rate of BRONJ after IV administration of bisphosphonates has been documented from 0 to 28 % and not more than 4 % in cases of oral BPs administration.…”
Section: Introductionmentioning
confidence: 75%
“…In the IORN cases numerous osteoclasts could be detected close to vital bone. In 2013 Sharma et al reported that BRONJ was characterized by presence of osteocyte-depleted bone lacunae which was more commonly seen in the deeper layers of the bone while lacunae located towards the surface of the bone lamellae will lose the osteocytes at a later stage [6,46]. Recently specimens of BRONJ/IORN tissues show necrotic bone surrounded by many bacterial colonies.…”
Section: Histopathologic Featuresmentioning
confidence: 99%
“…The combination of ASCs and PRP appears to be synergistic, and the addition of BMP-2 could further improve the results. (Yamada et al, 2009;Anavi-Lev et al, 2013;Sharma et al, 2013). Therefore, it seems that stimulating angiogenesis locally could be an effective management strategy.…”
Section: Introductionmentioning
confidence: 99%